The role of methylene blue in mitigating surgical morbidity in parotid surgery: a comprehensive review - Subhash, Soumith; Bagchi, Udit; Ethiraj, Suraj (International Surgery Journal, 2023)
Parotid surgery is associated with specific surgical morbidity, including temporary facial weakness, permanent facial nerve injury, post-parotidectomy depression, and Frey’s syndrome (gustatory sweating). Despite various modifications implemented to reduce surgical morbidity, complications, particularly facial nerve injury, remain a challenge. To overcome this difficulty, the use of an identification method, such as preoperative intravital staining of the gland with methylene blue (MB), has been proposed. This article provides a comprehensive review of the role of MB in parotid surgery, discussing its potential benefits, safety profile, and future directions for research.